The past and the future of the Euro - Arestis, Philip (Revista de Economía Crítica, 2024)
This contribution discusses the experience of the euro, and the extent to which its future is promising. The discussion begins with the Economic and Monetary Union (EMU) theoretical framework and policies, and adopted by the European Central Bank (ECB), and the extent to which fiscal policy, pursued by the EMU member countries, and monetary policy, pursued by the ECB, have been successful. The theoretical background of this approach is based on the New Consensus Macroeconomics (NCM), but it differs; and this is elaborated upon and discussed extensively. This discussion inevitably includes the post Global Financial Crisis (GFC), the Great Recession (GR) and the euro-crisis period in an attempt to examine the consistency of the theoretical background and the fiscal and monetary policies pursued. In terms of the future of the euro, the discussion just suggested enables this contribution to conclude that the extent to which the euro would survive requires further economic policies. Such policies, in addition to the current monetary policy, should be especially proper EMU fiscal policy, and other policies as discussed in this contribution. In effect this amounts to the suggestion that political integration is what is required to enable the euro to survive in the future.